2001
DOI: 10.1086/319092
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Hubble Space Telescope[/ITAL] Proper-Motion Measurements of the η Carinae Nebula

Abstract: We present proper-motion measurements of the bipolar lobes and equatorial disk features ejected from h Carinae during the last century and deduce their relative ages in order to determine the likelihood of multiple ejection events. Hubble Space Telescope Wide Field Planetary Camera 2 images taken in 1994, 1995, and 1999 were compared, and the motions of small (∼1Љ) patches throughout the nebula were measured. Assuming that the material has not been accelerated or decelerated, the projected expansion velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 18 publications
8
137
1
Order By: Relevance
“…The far-infrared emission originates from the circumstellar dust envelope around η Car. The famous bipolar Homunculus Nebula is thought to be the result of the "Great Eruption" in the 1840's (see Smith et al 1998;Currie & Dowling 1999;Morse et al 2001;Smith 2005;Artigau et al 2011;Davidson & Humphreys 2012). The total dust + gas mass in the bipolar nebula and a dense equatorial torus in the Homunculus is estimated to be about 15−20 M (Morris et al 1999;Smith et al 2003).…”
Section: The Far-infrared Spectral Energy Distribution Of η Carinaementioning
confidence: 99%
“…The far-infrared emission originates from the circumstellar dust envelope around η Car. The famous bipolar Homunculus Nebula is thought to be the result of the "Great Eruption" in the 1840's (see Smith et al 1998;Currie & Dowling 1999;Morse et al 2001;Smith 2005;Artigau et al 2011;Davidson & Humphreys 2012). The total dust + gas mass in the bipolar nebula and a dense equatorial torus in the Homunculus is estimated to be about 15−20 M (Morris et al 1999;Smith et al 2003).…”
Section: The Far-infrared Spectral Energy Distribution Of η Carinaementioning
confidence: 99%
“…This nebula, with an estimated mass ∼1M , consists of a two-lobe structure divided by a thin equatorial torus. Morse et al (2001) performed a proper motion study in this nebula by comparing HST images taken at three different epochs and concluded that the "Homunculus" also shows a single Hubble law and was formed in less that 10 yr during the great eruption in the 1840's. These measurements are only done in the plane of the sky (neither the position nor the velocities are derived along the line of sight, as in our case), so they do not depend on the orientation of the nebula or on the distance.…”
Section: The Origin Of the Ppn M 1-92mentioning
confidence: 99%
“…The polarimetric properties of the Egg are discussed elsewhere (Sahai et al 1998;Weintraub et al 2000;Ueta et al 2005b). To determine proper motion of the nebulosity over the 5.5 yr time interval defined by these two-epoch observations, we followed the method elucidated by Currie et al (1996) and Morse et al (2001) in their proper-motion measurements of Car. This method is based on the idea that proper motion of any local structure in a nebula due to an expansion can be measured by determining the amount of translational shift of the structure via a cross-correlation analysis.…”
Section: Proper-motion Measurementsmentioning
confidence: 99%